Pengembangan User Interface Aplikasi Guide Me! Berbasis Web dengan Pendekatan Human-Centered Design - Mohamad Rendiansah; Hanifah Muslimah Az-Zahra; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Traveling is an activity that can be done for spending holiday. However, the tour guide is still limit so that Guide Me! was made. Guide Me! is a system web-based that can help traveler who visited East Java for searching tour guide. This research focus on how developing user interface Guide Me! with involving user. A Method that can be involve user through the development is Human-Centered Design (HCD). HCD is a method for developing interactive system that focusing on making system that can be used and useful. This research will discuss about developing user interface Guide Me! from context of use, user requirement, making design solution and evaluating design solution. The result from this research showed that user interface design after applied HCD had better usability than before applied HCD. For effectivity aspect, the result was 96% for traveler and 96% for tour guide. For efficiency aspect, average time result was decreased than average time result in first design. Then, for user satisfaction, the result was better because it has fifteen statements good and only one statement bad for traveler and thirteen statements good and three statements bad for tour guide.